Urgensi Penerapan Qawaid al-Fiqhiyyah dalam Kehidupan Muamalah Sehari-hari : Studi Kualitatif di Kalangan Mahasiswa - Anza Zatira Pane; Nanda Ariska; Tithazzahra Autinsa; Abdul Rahman Sofyan (Maeswara : Jurnal Riset Ilmu Manajemen dan Kewirausahaan, 2026)
This study examines students’ understanding and application of Qawāʿid al-Fiqhiyyah in their daily muamalah practices and its implications for their ethical behavior. Using a descriptive qualitative approach, the research involved twenty students who provided data through questionnaires, in-depth interviews, and observations. The findings indicate that most students possess a solid understanding of the function of legal maxims as general principles guiding Islamic legal reasoning and as analytical tools for addressing contemporary issues. They are able to apply Qawāʿid al-Fiqhiyyah in various modern activities, such as digital transactions, social interactions, and financial management, which helps them act with greater caution, fairness, and responsibility. Nevertheless, several challenges remain, including difficulties in understanding Arabic terminology, limited contextual examples, and environments that do not always support consistent application. This study concludes that strengthening practical understanding and contextual learning is essential for Qawāʿid al-Fiqhiyyah to function effectively as a moral and Sharia-based guide for students navigating the complexities of modern life.